Comparative study of text clustering using k-means and self-organizing map algorithm [electronic resource] - Chew, Cher Yeung, 1987-; Ali Selamat, supervisor; Fakulti Komputeran (2015)
Thesis (Sarjana Sains (Sains Komputer)) - Universiti Teknologi Malaysia, 2015